Systematic Review: Success Rate of Endoscopic Endonasal versus Combined Endonasal and Transorbital Neuroendoscopic Approach for Nontraumatic Cerebrospinal Fluid Leak Repairs in the Lateral Recess of Sphenoid Sinus - Ahmed, Umnia Nasir; Siddiqui, Mohammed Saqlain; Iftikhar, Haissan; Jolly, Karan; Nieto, Hannah; Muzaffar, Jameel (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Cerebrospinal fluid (CSF) leaks from the lateral recess of the sphenoid sinus (LRS) occur due to a skull base defect and are important to treat due to the associated morbidity, e.g., life-threatening meningitis. Nontraumatic CSF leaks have a predilection toward obesity which is a rising phenomenon. LRS is notoriously difficult to access because of its lateral location and its associated neurovascular complications. An alternative surgical corridor has been explored which is the transorbital neuroendoscopic (TONES) approach.Objective To compare the success rate of the endoscopic endonasal with the TONES approaches.Rationale This is the first systematic review on the endoscopic endonasal and combined transorbital approaches to treat CSF leaks from the LRS.Method A PRISMA-concordant systematic review. PubMed, MEDLINE, EMBASE, Web of Science, and SCOPUS were searched. The studies underwent abstract and full-text screening by two reviewers. The data collected included patient demographic, surgical approach, reconstruction method, layers and materials, follow-up period, ROBINS-I bias, complications, and success rate.Results In total, 26 of 4,385 studies were included for further synthesis. Of these studies, a total of 336 patients were identified from a cohort of 910 patients. The endoscopic endonasal approach showed a repair success rate of 95.24% and the combined TONES and endonasal approach showed a success rate of 100%.Conclusion Both the endoscopic endonasal and transorbital approach provide a good success rate. However, due to the small TONES sample, large, randomized control trials are needed.
Keywords: lateral recess of the sphenoid sinus; cerebrospinal fluid leak; skull base; spontaneous; transpterygoid; TONES